2021
DOI: 10.1029/2020jd033094
|View full text |Cite
|
Sign up to set email alerts
|

A Computationally Efficient Ensemble Filtering Scheme for Quantitative Volcanic Ash Forecasts

Abstract: Volcanic eruptions have a significant economic impact on airline operations. As volcanic ash is a recognized hazard to flying aircraft, mainly because of its negative effects on engine performance (Casadevall, 1994), diversion of normal flight routes and grounding of aircraft is sometimes necessary to avoid encounters with airborne ash during volcanic eruptions. Ever since the eruption of the Icelandic volcano Eyjafjallajökull, in 2010, which had a significant impact on airline operations over Europe, there ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…The definition of sufficient needs to be explored further and is an issue of concern to all methods requiring selection of members from an ensemble. For instance, sufficient observations are required, alongside a shrewd choice of metric thresholds, for robust performance of the particle filtering methods employed by Zidikheri and Lucas (2021) and Capponi et al (2021). Insufficient observations will lead to similar metric values and an inability to determine the good ensemble members from the pack.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The definition of sufficient needs to be explored further and is an issue of concern to all methods requiring selection of members from an ensemble. For instance, sufficient observations are required, alongside a shrewd choice of metric thresholds, for robust performance of the particle filtering methods employed by Zidikheri and Lucas (2021) and Capponi et al (2021). Insufficient observations will lead to similar metric values and an inability to determine the good ensemble members from the pack.…”
Section: Discussionmentioning
confidence: 99%
“…Often a single estimate of emissions is obtained as the optimal value for the metric used or, in the Bayesian framework, as the peak of the posterior distribution, and this is used to forecast the transport and dispersion of the volcanic cloud with the atmospheric dispersion model. Source inversion techniques can also yield a range of solutions, for example, by selecting all solutions with metric values above a threshold or by making better use of the posterior probability distribution function, leading to probabilistic forecasts (Capponi et al., 2021; Zidikheri & Lucas, 2021). Further work on interpretation and use of probabilistic information in an operational setting is, however, required.…”
Section: Review Of Inversion Techniques For Estimating Volcanic Emiss...mentioning
confidence: 99%
See 2 more Smart Citations
“…This enables a considerable reduction in the number of control variables when the method is applied to eruptions in real time, thereby making it computationally tractable in operational contexts. Furthermore, it was shown that the "curse of dimensionality" that afflicts all ensemble filtering schemes, in which ensemble size is at times too severely diminished by the algorithm, could be ameliorated by dividing the ensemble members into smaller batches and applying the algorithm to each batch rather than to the whole ensemble [22]. The ensemble filtering method can also be used to reject poor retrievals or detections as initial fields when a direct data insertion scheme is used to initialize the dispersion models, as well as to find optimal top and base ash cloud heights, which can further improve forecasting skill, in some situations [23].…”
Section: Introductionmentioning
confidence: 99%